Catalysts informatics: paradigm shift towards data-driven catalyst design. Issue 16 (1st February 2023) - Takahashi, Keisuke; Ohyama, Junya; Nishimura, Shun; Fujima, Jun; Takahashi, Lauren; Uno, Takeaki; Taniike, Toshiaki
Abstract : This work summarizes how catalysts informatics plays a role in catalyst design. Abstract : Designing catalysts is a challenging matter as catalysts are involved with various factors that impact synthesis, catalysts, reactor and reaction. In order to overcome these difficulties, catalysts informatics is proposed as an alternative way to design and understand catalysts. The underlying concept of catalysts informatics is to design the catalysts from trends and patterns found in catalysts data. Here, three key concepts are introduced: experimental catalysts database, knowledge extraction from catalyst data via data science, and a catalysts informatics platform. Methane oxidation is chosen as a prototype reaction for demonstrating various aspects of catalysts informatics. This work summarizes how catalysts informatics plays a role in catalyst design. The work covers big data generation via high throughput experiments, machine learning, catalysts network method, catalyst design from small data, catalysts informatics platform, and the future of catalysts informatics via ontology. Thus, the proposed catalysts informatics would help innovate how catalysts can be designed and understood.